Детермінанти трансформації сільсько-міських агломерацій на засадах інклюзивності - Лопатинський, Юрій (My University, 2024)
У статті розглянуто питання становлення та подальшої трансформації сільсько-міських агломерацій. Наведено окремі напрями децентралізації управління та місцевого самоврядування в Україні, об’єднані територіальні громади визначено як прообраз сільсько-міських агломерацій. Виокремлено основні детермінанти, що впливають на розвиток сільсько-міських агломерацій: економічні, соціальні, демографічні, екологічні, інституційні, просторові. Зазначена специфіка галузевої направленості та соціально-просторової спрямованості розвитку сільсько-міських агломерацій. Окреслена методологічна роль інституційних засад трансформації сільсько-міських агломерацій і напрями необхідної новітньої інституційної трансформації. Підкреслена вагомість запровадження засад інклюзивності як запоруки подальшого сталого розвитку сільсько-міських агломерацій.
DETERMINANTS OF THE TRANSFORMATION OF RURAL-URBAN AGGLOMERATIONS ON THE BASIS OF INCLUSIVENESS
This article explores the formation and subsequent transformation of rural-urban agglomerations, emphasizing the importance of inclusivity in these processes. It delves into various aspects of decentralization and local governance in Ukraine, highlighting united territorial communities as precursors to rural-urban agglomerations. Additionally, the article contextualizes transformational processes as changes in existing institutional structures and the formation of new systems influenced by both endogenous and exogenous factors. It examines the concept of agglomeration as a form of territorial concentration of resources, creating a complex dynamic system with strong economic, social, and infrastructural links. For Ukraine, the significant size of its territory and the territorial remoteness of administrative units influence the territorial-sectoral distribution of the economy and settlement systems. The study identifies key determinants influencing the development of these agglomerations, including economic, social, demographic, environmental, institutional, spatial, and cultural factors. The research outlines the specifics of sectoral orientation and socio-spatial development. The problems related to the institutional and legal framework for the functioning of rural-urban agglomerations in Ukraine are presented, along with the methodological role of institutional foundations in the transformation of these agglomerations. The need for new institutional transformations is outlined, emphasizing the implementation of inclusiveness principles as a guarantee of sustainable development. The article concludes with a call for further institutional regulation and the promotion of inclusive development to address the issue of uneven territorial development and economic specialization in Ukraine. Recommendations for further development include institutional regulation, public-private partnerships, self-governance conditions, and inclusiveness. The article highlights the importance of tailored institutional changes and active community involvement in ensuring the effective transformation and development of these agglomerations.
Keywords: сільсько-міські агломерації, інклюзивний розвиток, детермінанти інклю- зивного розвитку сільсько-міських агломерацій, галузева направленість розвитку сіль- сько-міських агломерацій, соціально-просторова спрямованість розвитку сільсько-міських агломерацій, інституційні засади розвитку сільсько-міських агломерацій, трансформація сільсько-міських агломерацій; rural-urban agglomerations, inclusive development, determinants of inclusive develop- ment of rural-urban agglomerations, sectoral orientation of rural-urban agglomerations development, socio-spatial orientation of rural-urban agglomerations development, institutional foundations of rural- urban agglomerations development, transformation of rural-urban agglomerations